PERJALANAN KARIER SYAHIRAN: DARI CAMAT HINGGA BUPATI PASAMAN BARAT TAHUN (1982-2010) - Purnama, Sri; Husnita, Liza; Ersi, Livia (Pendidikan Sejarah, 2013)
ABSTRACTÂ Â The thesis discussed about the biography Syahiran of a formal choosen leader.Â  Syahiran is a leader who is very kind to other people or public. The problem of this research was how the way of his carier from a Subdistrict head (Ketua Camat) until become a regent (Bupati) of Â Pasaman Barat. The formulation of the problem in this research was how the history of Syahiranâs life and how did his role in increasing people progression during his leaderships in Pasaman Barat at 1982-2010.He was born at Tebingtinggi, September 9th, 1953. He started his carier as a staff of government, that was a Subdistrict head in 1982 at Batipuh, Tanah Datar and at 1989, he was choosen as the leader of Setda village in Pasaman. In 1991 Syahiran was also choosen as a Subdistrict head at Pasaman city at, and then, in 1993 he became a Subdistrict head again at Sungai Beremas, Pasaman. After that, in 1996, Syahiran was still chosen as Subdistrict head at Kinali, Pasaman and in 1998, he still tookhold as Subdistrict head at Rao Mapatunggul, Pasaman. After becoming a Subdistrict head for years, in 1999, Syahiran became an assistant Tata Praja Setda at Pasaman. Then, in 2001 he became an Economic Building Assistant Setda at Pasaman city and from 2001-2005 he became a secretary area (Sekretaris Daerah) at Pasaman. in 2005-2010 Syahiran decided to come to Politic which had known all the risk inside it. Therefore, he had been chosen as the Regent of Pasaman Barat that was voted by public directly.Keyword: figure, bureaucrat, politics, leader.